Ancient Worlds in Film and Television Gender and Politics - Renger, Almut-Barbara; Solomon, Jon (Metaforms, 2012)
This volume reinvigorates the field of Classical Reception by investigating present-day culture, society, and politics, particularly gender, gender roles, and filmic constructions of masculinity and femininity which shape and are shaped by interacting economic, political, and ideological practices. Readership: All interested in Classics, the Classical Tradition, Film Studies, Gender Studies, American Studies, Comparative Literature, Myth & Folklore, Religious Studies